2020
DOI: 10.3906/vet-1812-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Osteopontin gene variants on milk production traits in Holstein Friesian crossbred cattle of Kerala

Abstract: Osteopontin gene (OPN) is located in the quantitative trait loci (QTL) for milk production traits in bovine chromosome 6. In the present study the impact of cytosine to thymine transition in the intron-4 of OPN gene (g.8514C > T) on milk production traits was analysed in the Holstein Friesian crossbred cattle of Kerala. Genomic DNA was isolated and a fragment of 290 bp enclosing the polymorphic site was amplified and genotyped by restriction fragment length polymorphism (RFLP) using endonuclease, BSeN1. The ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…For PCR amplification, the components were optimized at 10 pM concentration and thermal cycling conditions were optimized at 53 o C annealing temperature. The 290 bp amplified products were digested with BsrI restriction enzyme as per the optimized PCR-RFLP protocol (Lali et al 2020) with some minor modifications. Restriction digestion was carried out using 5 Units of BsrI restriction enzyme, 1× buffer and molecular biology grade water.…”
Section: Spp1g1-bsri Pcr-rflp Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…For PCR amplification, the components were optimized at 10 pM concentration and thermal cycling conditions were optimized at 53 o C annealing temperature. The 290 bp amplified products were digested with BsrI restriction enzyme as per the optimized PCR-RFLP protocol (Lali et al 2020) with some minor modifications. Restriction digestion was carried out using 5 Units of BsrI restriction enzyme, 1× buffer and molecular biology grade water.…”
Section: Spp1g1-bsri Pcr-rflp Analysismentioning
confidence: 99%
“…conducted SPP1 gene polymorphism study at intron-4 using BsrI enzyme and reported fixation of TT genotype (290 bp) in 147 animals of Sahiwal and Haryana cattle breeds. Rahmatala and Brockmann (2015) investigated SPP1 polymorphism and its effects for milk traits in 60 Sudanese dairy cattle breeds and reported fixation of T allele Lali et al (2020). studied effect of Osteopontin gene polymorphism on milk traits in 144 animals of Holstein Friesian crossbred cattle of Kerala and reported frequency of TT, CT and CC genotype as 0.60, 0.32, 0.08 respectively.…”
mentioning
confidence: 99%
“…Al-Waith (2019) identified significant difference between two genotypes KK and KL with respect to milk yield (KK had higher milk yield) and fat per cent (KL had higher milk fat per cent). Inconsistent association analysis results could be the result of population substructure creation, null alleles in population or excessive selection pressure (Lali et al, 2020).Thus, A465G polymorphism can be suggested as a potential marker for obtaining a good selling price to a farmer for milk as the fat and SNF per cent in milk determines the milk pricing in Kerala.…”
Section: Association With Milk Production Traitsmentioning
confidence: 99%
“…This complex binds to adipophilin in the phospholipid bilayer of milk secretory granule and pinches off the mammary gland epithelial cell in zipper like fashion (Robenek et al, 2006). Many molecular markers in candidate genes for milk production such as Diacylglycerolo-transferase 1 (Lali and Anilkumar, 2016), Beta 1,4-galactosyltransferase-1 (Valsalan et al,2021), Leptin (Lali and Bindu, 2015) and Osteopontin (Lali et al, 2020) were studied in crossbred cattle of Kerala. It is worth to note that, majority of SNPs act as indirect markers and the influence on production traits depends on state of linkage disequilibrium (LD) in cattle.…”
mentioning
confidence: 99%
“…This may be due to the fact that OPN appears to play a key role in conception, implantation, and pregnancy maintenance. 14 Moreover, many variations have been identified in the OPN ( SPP1 ) gene with production traits in cattle, 15 and reproductive traits and litter size in pigs. 13 , 16 , 17 Based on the above literature review, very few studies have been conducted on genetic polymorphisms in the OPN gene in relation to their association with cattle prolificacy, and to the best of our knowledge, no studies have been conducted regarding their association with sheep prolificacy.…”
Section: Introductionmentioning
confidence: 99%